Pengaruh Harga dan Media Sosial Instagram Terhadap Minat Beli Handphone Oppo pada Toko Oppo di Plaza Millenium - Parlindungan Purba; Herniwati Tafonao (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The purpose of this study is to determine the impact of price and Instagram social media on consumer interest in purchasing Oppo mobile phones at Plaza Millennium. The impact between price and Instagram social media is partially and simultaneously analyzed with respect to purchase intent. The research method used is quantitative research. The data collection technique used questionnaires distributed directly to his Oppo shop in the Plaza Millennium using a targeted sampling technique. The sample for this survey was her Oppo mobile customer at the Millennium Plaza. The analytical methods used are validity testing, reliability testing, classical acceptance testing, multiple linear regression analysis, and hypothesis testing. The results of the research conducted show that price variables have a significant impact on consumer purchasing intentions. This is shown by the results of a partially run test (t-test) on the SPSS program, where tcount (3.165) is greater than ttable (1.661). The value of tcount (3,709) is higher than ttable (1,661) because the Instagram social media variables have a greater impact on consumer purchase interest, and the price variable and Instagram social media have a greater impact on consumer purchase interest. fcount affects price. Instagram social media outperforms ftable (55,561 > 3.09).